New observations of NGC 1624−2 reveal a complex magnetospheric structure and underlying surface magnetic geometry. Issue 2 (14th December 2020) - David-Uraz, A; Petit, V; Shultz, M E; Fullerton, A W; Erba, C; Keszthelyi, Z; Seadrow, S; Wade, G A
ABSTRACT: NGC 1624−2 is the most strongly magnetized O-type star known. Previous spectroscopic observations of this object in the ultraviolet provided evidence that it hosts a large and dense circumstellar magnetosphere. Follow-up observations obtained with the Hubble Space Telescope not only confirm that previous inference, but also suggest that NGC 1624−2's magnetosphere has a complex structure. Furthermore, an expanded spectropolarimetric time series shows a potential departure from a dipolar magnetic field geometry, which could mean that the strongest field detected at the surface of an O-type star is also topologically complex. This result raises important questions regarding the origin and evolution of magnetic fields in massive stars.